DNA-GEL, Novel Nanomaterial for Biomedical Applications and Delivery of Bioactive Molecules - Enrico Lattuada; Manuela Leo; Debora Caprara; Luisa Salvatori; Antonella Stoppacciaro; Francesco Sciortino; Patrizia Filetici (Frontiers Media S.A., 2020)
Novel DNA materials promise unpredictable perspectives for applications in cell biology. The realization of DNA-hydrogels built by a controlled association of DNA nanostars, whose binding can be tuned with minor changes in the nucleotide sequences, has been recently described. DNA hydrogels, with specific gelation properties that can be reassambled in desired culture media supplemented with drugs, RNA, DNA molecules and other bioactive compounds offer the opportunity to develop a novel nanomaterial for the delivery of single or multiple drugs in tumor tissues as an innovative and promising strategy. We provide here a comprehensive description of different, recently realized DNA-gels with the perspective of stimulating their biomedical application. Finally, we discuss the possibility to design sophisticated 3D tissue-like DNA-gels incorporating cell spheroids or single cells for the assembly of a novel kind of cellular matrix as a preclinical investigation for the implementation of tools for in vivo delivery of bioactive molecules.